2006
DOI: 10.1016/j.visres.2005.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Form-deprivation myopia in the guinea pig (Cavia porcellus)

Abstract: Form deprivation (FD) was induced in 61 guinea pigs with a diffuser worn on one eye. The form-deprived eye elongated and developed myopia within 6 days in animals raised under a 12:12 h light/dark cycle, but not when reared in darkness. After 11 days of FD, the average eye was -6.6 D more myopic and 146 microm longer than its fellow eye. Initially the myopia was mostly from vitreous chamber elongation, but with longer periods of FD, corneal power increases predominated. These effects were confirmed in schemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
175
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(179 citation statements)
references
References 60 publications
4
175
0
Order By: Relevance
“…The guinea pig develops deprivation myopia in a short period of time [4] with independent growth in different retinal hemifields [29] and responds to lensinduced blur [30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The guinea pig develops deprivation myopia in a short period of time [4] with independent growth in different retinal hemifields [29] and responds to lensinduced blur [30].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, longitudinal studies of myopia development can occur within a much shorter time period than in humans. The guinea pig has been established as an effective myopia model, and stands as a common myopia model in Asian research labs today [4]. It is a mammal, shows a rapid ocular development, responds to lens-induced blur, is easy to raise and handle, and optical measurements are feasible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…83 Another early study on chicks found that monocular deprivation of form vision also produced myopia and eye enlargement. 84 These landmark studies ushered a new era in experimental myopia study and in the years since, models of form deprivation of myopia have been developed in a wide variety of animal species, including chicks, 85,86 tree shrews, 87,88 guinea pigs 89,90 and adult monkeys. 91 Other experimental methods using positive or negative lens as modulators of refractive error in chicks showed that the eye grows more slowly (developed hyperopia) or more rapidly (developed myopia), respectively.…”
Section: Animal Models Of Myopiamentioning
confidence: 99%
“…Form deprivation was induced with a translucent diffuser as previously described, 22 and diffusers were cleaned and checked daily. At the end of 2 weeks, one drop of 1% cyclopentolate (Cyclogyl; Alcon, Macquarie Park, Australia) was topically applied to each eye and after 1.25 to 1.5 hours, the refractive error was measured using an infrared autorefractor (AR-20Nidek; Gamagori, Aichi, Japan).…”
Section: Induction Of Myopia and Ocular Measuresmentioning
confidence: 99%